Morphologic, viability and ultrastructural analysis of vitrified sheep preantral follicles enclosed in ovarian tissue - Lunardi, Franciele Osmarini (2012)
The main objective was to compare the efficiency of vitrification techniques and solutions on the preservation of morphology, ultrastructure and viability of sheep preantral follicles enclosed in ovarian tissue fragments. The fragments were cryopreserved by using macrotube vitrification (MTV), solid-surface vitrification (SSV) or conventional vitrification (CV). These techniques were combined with one of the six solutions containing 6 M ethylene glycol (EG) and with or without sucrose (SUC) (0.25 or 0.50 M) and with or without fetal calf serum (FCS) (10%). After one week, samples were warmed and histological analysis was performed, showing that the percentage of normal follicles after CV (66.20 ± 8.87%) using a solution containing 6 M EG, 0.25 M SUC and 10% FCS (vitrification solution 4 – VS4) was similar to fresh control (79.40 ± 7.83%), MTV (53.40 ± 10.60%) and SSV (56.75 ± 15.33%), all of them with the same vitrification solution (P < 0.05). For follicular viability evaluation, ovarian fragments were vitrified as described above. After warming, follicles were assessed by trypan blue dye. Controversially, the highest percentage of viable follicles was observed in MTV (97.06%) and was similar to fresh control (92.62%) (P < 0.05), but was significantly different from SSV (81.08%) and CV (83.81%) (P < 0.05). These results were validated by transmission electron microscopy that showed normal follicles observed in MTV and in fresh control. In addition, to verify the MTV with VS4 (a combination of the best technique plus the best solution), follicle viability was evaluated after 48 h in vitro culture. The viability assay was performed by fluorescence microscopy (calcein-AM and ethidium homodimer-1) analysis as follows: follicles isolated from fresh tissue were forthwith analyzed or underwent 48 h in vitro culture before analysis, whereas others fragments were vitrified/warmed and immediately analyzed or underwent 48 h in vitro culture before analysis. These results showed that, although follicular viability after MTV/VS4 (65%) was reduced when compared to the non-vitrified follicles at day 0 (100%), follicular viability after MTV/VS4 at day 2 (36.5%) was similar to follicles vitrified at day 0 (65%) and similar to non-vitrified follicles at day 2 (62.5%) (P > 0.05). As the decrease of viability in non-vitrified follicles at day 2 was similar to the decrease of MTV/VS4 in the same time, follicle viability at day 2 is not affected by MTV/VS4. In conclusion, using the experimental conditions of the present study, an efficient solution (VS4: 6 M EG, 0.25 M SUC and 10% FCS) and technique (MTV) were successfully used to vitrify ovine ovarian tissue.